L’impact De La Création Des PME/PMI Sur L’idh En Algérie « Étude Économétrique 2001-2013 » - Rédha, Bouchikhi Mohamed; Mohamed, Yagoub (European Scientific Journal, ESJ, 2017)
One of the major problems faced by the Algerian economy is sustainability. This is because the economy is essentially hydrocarbon-based. Since 2001, Algeria has adopted a new strategy to strengthen and diversify the economic sector in order to reduce poverty and ensure sustainable development. This study aims to highlight the impact of these reforms on the development and the level of well-being. For this purpose, we carried out an econometric study over the period (2001-2013) in order to ascertain the impact of the creation of SMEs on the improvement of the quality of life which is measured in this test by the HDI. We found that the strategy adopted by the Algerian state for the creation and promotion of SMEs in Algeria has a positive impact on the state of development of the country and the level of well-being of the population.